PERFORMANCE ANALYSIS OF THE WARMADEWA EDUCATIONAL HOSPITAL BUILDING CONSTRUCTION PROJECT - Ni Made Jero Suarmini; I Wayan Gde Erick Triswandana; Kadek Windy Candrayana (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
In a project, effective management is crucial for organizing workflow and control to achieve the project's objectives. Project management involves continuous monitoring and evaluation of project performance to ensure that all parts of the project are on track. The aim of this study is to analyze the performance of the Warmadewa Educational Hospital Building Construction Project in terms of cost and time using the Earned Value method. The data used consists of primary data obtained from field observations and interviews, as well as secondary data from weekly reports, the Budget Plan (RAB), and the project schedule. The analysis shows that the project experienced delays from the first week up to the evaluation week. The Schedule Variance (SV) and Schedule Performance Index (SPI) analysis indicates that the project is progressing slower than planned. From the Estimate To Complete (ETC) and Estimate At Completion (EAC) analyses, the project is estimated to require an additional 719 days to complete. This represents a delay of 92 days from the initial planned duration of 627 days. The Cost Variance (CV) and Cost Performance Index (CPI) analysis indicate that the project costs are within the budget.